Transcriptomic analysis reveals the inhibition of reproduction in rice brown planthopper, Nilaparvata lugens, after silencing the gene of MagR (IscA1). Issue 3 (11th January 2021) - Liu, X.; Chen, G.; He, J.; Wan, G.; Shen, D.; Xia, A.; Chen, F.
Abstract: MagR (IscA1) is a member of the iron–sulphur cluster assembly proteins, which plays vital roles in many physiological processes, such as energy metabolism, electron transfer, iron homeostasis, heme biosynthesis and physiologically magnetic response. Its deletion leads to the loss of mitochondrial DNA, inactivation of iron–sulphur proteins and abnormal embryonic development in organisms. However, the physiological roles of MagR in insects are unclear. This study characterized the effects and molecular regulatory mechanism of MagR gene silencing on the reproduction of brachypterous female adults of Nilaparvata lugens . After silencing the MagR gene using RNAi approach, the duration of reproductive period was shortened and the fecundity and hatchability reduced significantly. A total of 479 differentially expressed genes (DEGs) were identified for female adults after 2 days of dsRNA injection through RNA‐sequencing technology, including 352 significantly upregulated DEGs and 127 significantly downregulated DEGs, among which 44 DEGs were considered the key genes involved in the effects of NlMagR silencing on the reproduction, revealing the regulatory mechanism of MagR at RNA transcription level and providing a new strategy for the control of N. lugens .